Phosphorus : past and future - Elser, James J., 1959-; Haygarth, Philip M. (Oxford University Press, 2021)
Phosphorus is essential to the production of our food, and it also triggers algal blooms in lakes, rivers, and oceans when it slips through our hands. An understanding of this essential resource and how we have used and misused it over the years is crucial to the sustainability of our well-being on our planet. In this book, world authorities on phosphorus sustainability Jim Elser and Phil Haygarth explain this element's involvement in biology, human health and nutrition, food production, ecosystem function, and environmental sustainability. Phosphorus chronicles the sustainability challenges phosphorus both poses and solves in various contexts. The book begins with its discovery over 350 years ago, moving to its basic chemistry and the essential role it plays in all living things on Earth. Chapters go on to explain the rise in the usage of phosphorus in agriculture and how the increase in the mining of rock phosphate in the mid-20th century was essential for the Green Revolution. However, phosphorus emissions from human wastes and detergents triggered widespread algal blooms in the 1960s and 1970s. While such emissions have been brought under better control with wastewater treatment, diffuse emissions from farming continue to cause water quality degradation. The authors explain how these diffuse phosphorus emissions may worsen with climate change. In ten concise chapters, Elser and Haygarth offer engaging explanations of our historical use and abuse of phosphorus, including the phosphorus sustainability movement and new efforts to sustain food benefits of limited rock reserves following the phosphate rock price shock in 2007-2008. Highlighting new approaches for phosphorus, the two 'Systems Innovators' turn toward the emerging set of sustainable phosphorus solutions necessary to achieve a sustainable 'phosphoheaven' and avoid 'phosphogeddon.' The book provides an insider's take on this essential resource and why all of us need to wrestle with the wicked problems this element will cause, illuminate, or eliminate in years to come.